La gobernanza electoral en el Ecuador, durante el periodo 2011 - 2013: construyendo el camino hacia la democracia de calidad en el Ecuador. - Pavón Villacrés, Karla Lorena. (2018)
In this research analyzed the correlation between these theoretical concepts with: a) Democracy, b) Quality of Democracy and c) Electoral Governance and the institutional mechanisms set by the National Electoral Council under this new scenario for the period 2011-2013. It was established that democracy is the means by which the states strengthen their interaction with the public through public policies that guarantee their rights and freedoms, which are realized through institutions such as the National Electoral Council, the body that strengthens the processes democratic and guarantees the rights of political and civic participation. But how these guarantees are operationalized? Designing and institutionalizing mechanisms for institutional internal governance (constitutional law and internal regulations) and management (independence, professionalism, civic and democratic education and speed in the delivery of results), which no doubt has contributed to strengthening the quality of democracy in its dimension of reciprocity (legitimacy) according to the results obtained by the level of trust given by the citizens and political support of political organizations to the institutions of the National Electoral Council for the management given 2011-2013 period where "Build democracy ".